Pelatihan Pengelolaan dan Penyusunan Laporan Keuangan Berbasis Digital Berdasarkan Standar Akuntansi Keuangan untuk Pelaku UMKM - Lucyanda, Jurica; Hatta, Holila; Julian, Muhammad Arvi Gelar; Fathulloh, Iqbal; Hasbie, Raka Muhammad; Asa, Sarah Novita (Indonesian Journal for Social Responsibility, 2025)
Community service (PkM) aims to increase the knowledge and understanding of micro, small, and medium enterprises (MSMEs) and the importance of accounting and financial statements in a business. Currently, the Government of Indonesia is focusing on developing MSMEs as a main foundation of the economic sector to encourage the ability to be independent in developing their businesses. However, the problem faced by MSMEs is that many have not prepared financial statements, especially based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This is due to the lack of knowledge and understanding of financial management and financial statements.  Based on these problems, it is necessary to give training in digital-based financial reports for MSMEs based on SAK EMKM. The community service method is training in accounting and financial reporting using SAK EMKM.  In addition, digital-based financial reports use the CrediBook application, making it easier for MSMEs to record business transactions. The partner of this PkM is a group of women (PKK) RW 02, Pancoran, South Jakarta, who produce cheese sticks under the brand "My Cheese". The results of this community service show that the participants gained increased knowledge and understanding of financial management and financial statements based on SAK EMKM. The increase can be seen from the pre-test and post-test results conducted on the training participants. The training resulted in a 75% increase in understanding of management and financial statements (from 25% to 100%) and an 87.5% increase in knowledge about SAK EMKM (from 12.5% to 100%).